Implications of Surface and Bulk Properties of Abutment Implants and Their Degradation in the Health of Periodontal Tissue - Avila, Erica Dorigatti de [UNESP]; Molon, Rafael Scaf de [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Mollo, Francisco de Assis [UNESP] (Mdpi Ag, 2013)
The aim of the current review was to investigate the implications of the surface and bulk properties of abutment implants and their degradation in relation to periodontal health. The success of dental implants is no longer a challenge for dentistry. The scientific literature presents several types of implants that are specific for each case. However, in cases of prosthetics components, such as abutments, further research is needed to improve the materials used to avoid bacterial adhesion and enhance contact with epithelial cells. The implanted surfaces of the abutments are composed of chemical elements that may degrade under different temperatures or be damaged by the forces applied onto them. This study showed that the resulting release of such chemical elements could cause inflammation in the periodontal tissue. At the same time, the surface characteristics can be altered, thus favoring biofilm development and further increasing the inflammation. Finally, if not treated, this inflammation can cause the loss of the implant.
Keywords: abutment implants; bacterial adhesion; cell adhesion; titanium; zirconia